Behaviour of Excess Stock Return Around Earnings Announcement Day: A Test of the Efficiency of the Kuala Lumpur Stock Exchange - Ahmadu Umaru Sanda,; Ang Ji Li,; G. S. Gupta, (Asian Academy of Management Journal, 1998)
Behaviour of Excess Stock Return Around Earnings Announcement Day: A Test of the Efficiency of the Kuala Lumpur Stock Exchange(PDF not available)